MENINGKATKAN KETERAMPILAN LITERASI INFORMASI MASYARAKAT MELALUI PROGRAM WISATA LITERASI - Prasetyo, Hendi; Rini, Heru (BACA: Jurnal Dokumentasi dan Informasi, 2024)
Information literacy has a very important role in everyday life. This study aims to describe literacy tourism destinations and efforts to improve people’s information literacy skills through literacy tourism programs. The research method uses a qualitative approach, data collection techniques use literature studies by utilizing various sources obtained from books, scientific articles in journals, and various other sources obtained on the internet. The results show that 1) libraries, reading houses, community reading parks, reading corners, and the like can be used as appropriate literacy tourism destinations to improve information literacy skills and obtain relevant information. 2) Improving public information literacy skills. The literacy tourism program can be carried out by holding various program activities such as library tours, user education, giving rewards, storytelling, educational games, as well as digitizing facilities and services. The research concludes that the literacy tourism program is very important to improve the information literacy skills of the community. Many libraries, reading houses, community reading parks, reading corners, and the like can be used as appropriate literacy tourism destinations in order to improve people’s information literacy skills. Researchers suggest that the government, libraries, literacy activists, and the community work together in an effort to improve literacy skills and culture in Indonesia.